Investigation of Impact-Ionization-Enhanced Effect on SiC Thyristors Triggered by Weak UV Light - Yulei Zhang; Xi Wang; Lechen Liu; Xuan Ji; Junhui Hou; Hongbin Pu (Micromachines, 2025)
The impact-ionization-enhanced mechanism is introduced into a SiC light-triggered thyristor (LTT) to improve its switching speed under weak UV illumination. The effects of impact ionization on photogenerated carrier multiplication and the dynamic switching performance of the SiC LTT are investigated through TCAD simulation. The relationships between bias voltage, UV light intensity, and key dynamic parameters are analyzed. Simulation results indicate that when the bias voltage exceeds 14 kV, the device enters the avalanche multiplication regime, leading to a significant increase in photocurrent under a given UV intensity. As the bias voltage increases, the turn-on time of the thyristor first decreases, then saturates, and finally drops rapidly. Under UV illumination of 100 mW/cm2, the turn-on time decreases from 10.1 μs at 1 kV to 0.85 μs at 18 kV, while the switching energy dissipation at 18 kV is only 1292.3 mJ/cm2. These results demonstrate that the impact-ionization-enhanced effect substantially improves the switching performance of SiC LTTs.